Sequencing and characterization of the complete mitochondrial genome of Thinopyrum obtusiflorum (DC.) Banfi, 2018 (Poaceae). Issue 3 (4th March 2022) - Wu, Xiaojun; Hu, Xigui; Chen, Xiangdong; Zhang, Jinlong; Ren, Cuicui; Song, Lintong; Fang, Fang; Dong, Na; Hu, Tiezhu; Ru, Zhengang
Abstract: In this study, the mitochondrial genome of Thinopyrum obtusiflorum was sequenced, assembled, and annotated. The complete circular mitogenome of Th. obtusiflorum is 390, 725 bp in length and the overall A + T content of mitogenome is 55.61%. It harbors 33 protein-coding genes (PCGs), 21 transfer RNA genes (tRNAs), six ribosomal RNA genes (rRNAs), and 20 simple sequence repeats (SSRs). Phylogenetic analysis indicates that Th. obtusiflorum is a sister to the clade including Aegilops speltoides, Triticum aestivum, and Triticum aestivum cultivar Chinese Yumai in the Triticeae.